Juridical Review of International and National Law Relationships - Doris Rahmat (East Asian Journal of Multidisciplinary Research, 2023)
The Civil Law system tends (although not always) to be less receptive to the extradition of its citizens. As a result, their systems allow the exercise of jurisdiction over their citizens over offenses committed abroad. Common Law countries. Formulation of the problem how the relationship between international law and national law. This research is a normative legal research. This research studies law which is conceptualized as a norm or rule that applies in a society and becomes a reference for everyone's behavior. The approach used is a conceptual approach that departs from the views of experts and doctrines that have developed in international law and national law as a unified legal system in the pyramid of universal law so that international law has priority.